Rancang Bangun Sistem Pemantauan Kualitas Air Pada Perikanan Budidaya - Yaqin, Rizqi Ilmal; Pamaharyani, Luchiandini Ika; Priharanto, Yuniar Endri; Lagsmana, Tegar; Alip, Ahmad (Electrician : Jurnal Rekayasa dan Teknologi Elektro, 2024)
The utilization of microcontroller systems for monitoring water quality in aquaculture remains uncommon. Particularly, there is a pressing need for real-time monitoring of water quality to ensure optimal control in aquaculture operations. Hence, this research aims to assess the performance of an Arduino-based water quality monitoring system that has been developed. This system employs various sensors to monitor water quality and is centered around an Arduino microcontroller. Subsequently, the constructed system underwent testing using different solutions, including TDS solution calibrated to 1382 ppm, pH buffer solutions of pH 4.00, pH 6.86, and pH 9.00, as well as clean water and water from fish ponds. The measurement results obtained from the device were compared and analyzed for error rate, precision, and accuracy. The findings indicate that the system functions effectively with temperature, TDS, and pH sensors, exhibiting favorable error, accuracy, and precision values. Thus, the Arduino-based water quality monitoring system devised in this study proves to be a viable option for aquaculture operations. This research contributes novel insights into real-time water quality monitoring, enhancing the efficiency of water management in aquaculture.